Minor marriage in early Islamic law - Baugh, Carolyn. (Studies in Islamic Law and Society, 2017)
In Minor Marriage in Early Islamic Law , Carolyn Baugh offers an in-depth exploration of 8th-13th century legal sources on the marriageability of prepubescents, focusing on such issues as maintenance, sexual readiness, consent, and a father's right to compel. Modern efforts to resist establishment of a minimum marriage age in countries such as Saudi Arabia rest on claims of early juristic consensus that fathers may compel their prepubescent daughters to marry. This work investigates such claims by highlighting the extremely nuanced discussions and debates recorded in early legal texts. From the works of famed early luminaries to the "consensus writers" of later centuries, each chapter brings new insights into a complex and enduring debate.